REINTERPRETASI KONSEP MAHRAM DALAM PERJALANAN PEREMPUAN PESPEKTIF HERMENEUTIKA FAZLUR RAHMAN - Holilur Rohman (AL-HUKAMA, 2017)
Discuss the issue of women is no end. Every angle of women invites a discussion that must be done in depth, including the issue of hadith which describes the necessity of a mahrom for women when they want to travel. On the one side the necessity of mahram has a positive impact for the security and protection of women, but on the other side invites problems because the dynamics of women's lives today that require doing activities outside the home without having to be accompanied by mahrom. Really a dilemma for women. On the one side want to live his life according to the command of religion by following the hadith of the Prophet, but on the other side, when following hadith textualy will make her busy in activity outside the home. Therefore, this paper will discuss more deeply the problem of women's journey by reinterpretation mahram concept of Fazlurrahman hermeneutic perspective, in order to find the best solution for Muslim women in particular, for Muslims in general.